The vision of vision: semiotic of the editorial speech - Quezada-Macchiavello, Óscar (1985)
The present work deals with the special report entitled: "1981: Analysis. Goodbye to a year of changes, violence and hope "appeared in vol. 57, No. 12 of December 15/29, 1981 in the Inter-American Vision magazine.